2005
DOI: 10.1099/jmm.0.45872-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of inflammatory cytokines and nitric oxide in J774.2 cells and murine macrophages by lipoteichoic acid and related cell wall antigens from Staphylococcus epidermidis

Abstract: Staphylococcus epidermidis causes infections associated with medical devices including central venous catheters, orthopaedic prosthetic joints and artificial heart valves. This coagulase-negative staphylococcus produces a conventional cellular lipoteichoic acid (LTA) and also releases a shortglycerophosphate-chain-length form of LTA (previously termed lipid S) into the medium during growth. The relative pro-inflammatory activities of cellular and short-chain-length exocellular LTA were investigated in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Thus, LTA should be considered an important TLR2 ligand. LTA is readily released into culture supernatants and is abundant in them (32,57), whereas lipoproteins are primarily associated with bacteria and are not released into supernatants (45). In fact, consistent with our conclusions is the finding that the culture supernatant of the lipoprotein-deficient bacteria (⌬lgtA) is as inflammatory as wild-type bacterial culture supernatant (45).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, LTA should be considered an important TLR2 ligand. LTA is readily released into culture supernatants and is abundant in them (32,57), whereas lipoproteins are primarily associated with bacteria and are not released into supernatants (45). In fact, consistent with our conclusions is the finding that the culture supernatant of the lipoprotein-deficient bacteria (⌬lgtA) is as inflammatory as wild-type bacterial culture supernatant (45).…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, to evaluate the role of LTA in innate immune responses to gram-positive bacteria, we investigated the effects of inactivating LTA on the inflammatory properties of bacterial culture supernatants, which contain molecules that are shed or released from bacteria (24,26,32,46,54,57). Selective inactivation was possible since we have shown that plateletactivating factor acetylhydrolase (PAF-AH), a phospholipase A 2 , selectively inactivates staphylococcal and pneumococcal LTAs by removing their acyl-2 chain (44) but does not affect other acylated bacterial molecules, such as LPS and phosphatidylcholine (44).…”
mentioning
confidence: 99%
“…The use of IL-6 helped to distinguish between patients with infection and those without infection; however, other studies have indicated that IL-6 is not specific for detecting bacterial infection (18,37,39). IL-6 levels remained higher than the normal range also in the patients with previous infection, although to a lesser extent compared to patients with infection.…”
Section: Discussionmentioning
confidence: 92%
“…Its soluble forms (sICAM-1), both monomeric and dimeric, are generated by proteolytic cleavage (16)(17)(18)(19). The majority of molecules that bind ICAM-l are leukocyte integrins (LFA-l and Mac-) (20)(21)(22)(23), but also other types of molecules, including fibrinogen, rhinoviruses, and erythrocytes infected by Plasmodium falciparum can bind this molecule (24)(25).…”
mentioning
confidence: 99%
“…In animal models, lipoteichoic acid can induce features of sepsis such as delayed circulatory failure with hypotension and multiple organ failure [31]. Jones et al [32] demonstrated that the staphylococcal exocellular lipoteichoic acid is a potent activator of pro-inflammatory cytokines (TNF-a, IL-6 and IL-1) and nitric oxide in a murine macrophage cell line. The exocellular lipoteichoic acid is significantly more active than that of lipoteichoic acid, peptidoglycan or wall teichoic acid, especially for TNF-a and nitric oxide production.…”
Section: Discussionmentioning
confidence: 99%